The referral pattern of patients to periodontists by general dentists - Vaziri, Farzane; Zarifpour, Lina (Brazilian Dental Science, 2022)
Objective: The successful periodontal therapy needs a proper relationship between general dentist and periodontist. The aim of this study was to determine the referral pattern of patients to periodontists by general dentists in Yazd, Iran, by means of a questionnaire. Material and Methods: This descriptive cross-sectional study was carried out in the form of a survey among 145 licensed general dental practitioners in Yazd, Iran. A questionnaire comprising of seven questions with sub-questions was prepared. Results: 89% of dentists have referred patient to periodontist. Gingival recession was the most frequent reason for referring (69.7%) and the least was gingival bleeding (13.1%). The most frequent surgical procedure for what patients have been referred were peri-implantitis therapy and ridge augmentation. Referral status to periodontist for female dentists was 95.9% and for male dentists was 81.7%. The number of referred patients form the dentists who were practicing simultaneously at both private and public clinics was higher than those who were practicing only at private or public clinics. The most referral percentage was in the group of dentists with less than 5 years of experience with a slight difference from those with more than 10 years of experience. Only 26.1% of the respondents have participated in retraining programs. Conclusion: There is a need for general dentists to consider the primary signs of periodontal disease and necessity of referring the patients in early stages more serious, to provide an optimal long-term outcome for patients. KEYWORDS Dentist; Periodontal disease; Referral.